2000
DOI: 10.1046/j.1432-1327.2000.01527.x
|View full text |Cite
|
Sign up to set email alerts
|

Can yeast glycolysis be understood in terms of in vitro kinetics of the constituent enzymes? Testing biochemistry

Abstract: This paper examines whether the in vivo behavior of yeast glycolysis can be understood in terms of the in vitro kinetic properties of the constituent enzymes. In nongrowing, anaerobic, compressed Saccharomyces cerevisiae the values of the kinetic parameters of most glycolytic enzymes were determined. For the other enzymes appropriate literature values were collected. By inserting these values into a kinetic model for glycolysis, fluxes and metabolites were calculated. Under the same conditions fluxes and metab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
733
3
2

Year Published

2001
2001
2022
2022

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 620 publications
(763 citation statements)
references
References 121 publications
18
733
3
2
Order By: Relevance
“…Here two problems arise. First, it was found that in vitro kinetics do not reflect in vivo kinetics [19]. Second, for many enzymes in vitro kinetics are not available.…”
Section: Metabolic Reaction Network Models To Redesign Organisms: Redmentioning
confidence: 99%
“…Here two problems arise. First, it was found that in vitro kinetics do not reflect in vivo kinetics [19]. Second, for many enzymes in vitro kinetics are not available.…”
Section: Metabolic Reaction Network Models To Redesign Organisms: Redmentioning
confidence: 99%
“…When a number of enzymatic reactions interplay, based on enzymatic kinetics it has been shown that establishment of a stable state requires specific constraints on kinetic parameters, particularly maximal reaction activities [16,17,31,32]. In order to obtain a stable steady state based on the parameters in literature, many of the parameters need to be adjusted [33,34]. The constraints for formation of stable states in many interplaying enzymes are kinetic constraints for a biological network [17].…”
Section: Discussionmentioning
confidence: 99%
“…In case of estimating dynamic fluxes given an assumed objective, the results are compared with flux estimations based on concentration measurements in time and 13 C mass isotopomer measurements. In contrast to 13 C MFA, our method only uses metabolite concentration measurements (and not 13 C mass isotopomer measurements) to estimate the fluxes.…”
Section: Methodsmentioning
confidence: 99%
“…In contrast to 13 C MFA, our method only uses metabolite concentration measurements (and not 13 C mass isotopomer measurements) to estimate the fluxes.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation